Engineering mechanics. Statics. Statics study pack : chapter reviews, free-body diagram workbook, companion website - Hibbeler, R. C; Schiavone, Peter, 1961-; Hibbeler, R. C. (Upper Saddle River, NJ : Prentice-Hall, 2010)
Statics study pack was designed to help students improve their skills. It consists of three study components--a chapter-by-chapter review, a free-body diagram workbook, and an access code for the companion website
pt. 1 Chapter-by-chapter summaries -- pt. 2 Free-body diagram workbook
Accompanies: Engineering mechanics. Statics / R.C. Hibbeler. 12th ed
Keywords: Statics -- Problems, exercises, etc